Placenta Cretas: Early Diagnosis is Needed - Ismail, Hamizah; Nusee, Zalina; Chou, Min-Min (2011)
Incidence of placenta cretas increased in women who had previous caesarean or previous procedures for termination of pregnancy. The diagnosis of this emergency situation is often made at time of caesarean which could lead to increase maternal morbidity or even mortality. Placenta cretas had been reported to cause uterine rupture in early pregnancy. The availability of conventional 2D grayscale, color Doppler or the 3D power Doppler has changed the trend of time of the diagnosis made ie from at time of caesarean to as early as first trimester. These would give the advantage in anticipating and preventing complications. We demonstrate two cases of placenta increta one diagnosed at autopsy whereby presented as acute abdomen at 15 weeks of pregnancy and the other was diagnosed at 14 weeks by all the above ultrasound techniques. First case: A 35 year old G6 with previous one caesarean for her first pregnancy and two dilatation and curettage (D&C) procedures during her fourth and fifth pregnancies. At 15 weeks of pregnancy, she was brought to the emergency department for an acute abdomen following sexual intercourse. However her condition deteriorated to asystole. At autopsy there was a ruptured uterus over the uterine lateral-fundal measured 8 x 4.5 cm exposing sac of fetus. The histopathology was reported as placenta increta. Second case: A 33 year old G4 with two normal vaginal deliveries and a D&C for missed miscarriage during the third pregnancy. She first presented at 14 weeks for routine antenatal visit. 3D Power Doppler showed increased periplacental vascularity highly suggestive of morbidly adherent placenta. She was followed and had caesarean hysterectomy at 36 weeks with histopathology of placenta increta. Conclusion: Placenta cretas may lead to ruptured uterus and maternal mortality even in early pregnancy. In early pregnancy, prenatal diagnosis by ultrasound techniques is possible. Women with risk factors of placenta cretas need further ultrasound evaluation at the earliest stage of pregnancy.